2017
DOI: 10.3847/1538-4357/aa63e8
|View full text |Cite
|
Sign up to set email alerts
|

Surge-like Oscillations above Sunspot Light Bridges Driven by Magnetoacoustic Shocks

Abstract: High-resolution observations of the solar chromosphere and transition region often reveal surge-like oscillatory activities above sunspot light bridges. These oscillations are often interpreted as intermittent plasma jets produced by quasi-periodic magnetic reconnection. We have analyzed the oscillations above a light bridge in a sunspot using data taken by the Interface Region Imaging Spectrograph (IRIS). The chromospheric 2796Å images show surge-like activities above the entire light bridge at any time, form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 42 publications
6
38
0
Order By: Relevance
“…4 is caused by reconnection-related shock heating. Moreover, the intermittent and aperiodic occurrences of these jets also exclude the possible role of the p-mode wave on driving the jets, which is often suggested to account for the oscillating light walls above light bridges with a dominant period of several minutes (Yang et al 2015;Zhang et al 2017;Hou et al 2017;Tian et al 2018). One may see from the time-distance plots in Fig.…”
Section: Summary and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…4 is caused by reconnection-related shock heating. Moreover, the intermittent and aperiodic occurrences of these jets also exclude the possible role of the p-mode wave on driving the jets, which is often suggested to account for the oscillating light walls above light bridges with a dominant period of several minutes (Yang et al 2015;Zhang et al 2017;Hou et al 2017;Tian et al 2018). One may see from the time-distance plots in Fig.…”
Section: Summary and Discussionmentioning
confidence: 88%
“…The most prominent feature of light walls is their coherent oscillating bright fronts in 1330/1400 Å channel, which have rising speeds of about 10-20 km s −1 (Yang et al 2015). Zhang et al (2017) found that the core of the IRIS Mg ii k 2796.35 Å line within an oscillating light wall above a light bridge repeatedly experiences a fast, impulsive blueward excursion followed by gradual motion to a redshift. The authors proposed that these oscillating walls result from upward shocked p-mode waves.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 3 shows an example of the surge and the bright front ahead of the surge. Zhang et al (2017) analyzed the kinematics of such a bright front in another light bridge observation by IRIS, and found parabolic trajectories of the bright front. They also found a linear correlation between the maximum velocity and deceleration of the motion of the bright front, suggesting the nature of these long-lasting oscillatory motions to be slow-mode shock waves.…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 99%
“…Another sunspot element where asymmetry of the plasma environment could heavily influence wave propagation is the light bridge and corresponding light wall reaching up into higher layers of the atmosphere, which are trapped between two, sometimes vastly different umbral cores. Oscillations recently detected in light walls have been interpreted as signatures of propagating magneto-acoustic (shock) waves (Yang et al, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%